Design and fabrication of ergonomic gaming mouse / Muhammad Faris Azri Shamsulasri - Shamsulasri, Muhammad Faris Azri (2022)
The fast improvement of science and innovation causes the mouse to turn into the most generally utilized item life and work, but also the most frequent computer equipment, so users gradually the use of mouse proposed more requirements, including comfortable operation, flexible moving and accurate positioning, comfort discomfort for the most attention. The mouse also has its problems although various types of mouses have been invented thoroughly of the better good for its users. Moreover, the gaming mouse which is leading mouses than its peers seem to still offers appropriate users’ preferences levels that eliminate the problems above. Hence, the consensus is that gaming mouse selection and purchase should be individualized processes based on individual needs, work demands, usage period and ergonomic matter. The fast improvement of science and innovation causes the mouse to turn into the most